2021
DOI: 10.3389/fphar.2021.752211
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Action of Ziziphi Spinosae Semen in the Treatment of Insomnia: A Study Involving Network Pharmacology and Experimental Validation

Abstract: Purpose: This study aimed to investigate the potential mechanisms and related bioactive components of ZSS for the treatment of insomnia.Method: The insomnia model of rat induced by PCPA was established. After oral administration of ZSS extract, the general morphological observation, pentobarbital sodium-induced sleep test and histopathological evaluation were carried out. Network pharmacology, assisted by UHPLC-Q-Exactive-MS/MS analysis, was developed to identify the targets of ZSS in the treatment of insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Other aliphatic protons appeared in the region between δ 2.57 and 4.31. 13 C NMR and HSQC data revealed the presence of 20 carbon atoms, including nine sp 2 quaternary carbons, three sp 2 and one sp 3 CH, and three sp 3 CH 2 , which are characteristic signals of the aporphine alkaloid, [15] and the aporphine skeleton was confirmed by HMBC correlations from H-(6-NCH 3 , 2.87, 3H, s; 6-NCH3, 2.87, 3H, s) to C-5 (δ 60.4) and C-6a (δ 69.1); H-3 (δ 6.61, 1H, s) to C-4 (δ 23.2); H-8 (δ 6.38, 1H, d) to C-7 (δ 30.4). The HMBC correlations from H-(2-OCH 3 , δ 3.68, 3H, s) to C-2 (δ 151.1) and C-3 (δ 108.7) attached one methoxy group to C-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other aliphatic protons appeared in the region between δ 2.57 and 4.31. 13 C NMR and HSQC data revealed the presence of 20 carbon atoms, including nine sp 2 quaternary carbons, three sp 2 and one sp 3 CH, and three sp 3 CH 2 , which are characteristic signals of the aporphine alkaloid, [15] and the aporphine skeleton was confirmed by HMBC correlations from H-(6-NCH 3 , 2.87, 3H, s; 6-NCH3, 2.87, 3H, s) to C-5 (δ 60.4) and C-6a (δ 69.1); H-3 (δ 6.61, 1H, s) to C-4 (δ 23.2); H-8 (δ 6.38, 1H, d) to C-7 (δ 30.4). The HMBC correlations from H-(2-OCH 3 , δ 3.68, 3H, s) to C-2 (δ 151.1) and C-3 (δ 108.7) attached one methoxy group to C-2.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the literature either refers to Han et al's article [4] or reported MS data only. Moreover, many of the articles claimed there was magnoflorine present in the Semen Ziziphi Spinosae, [12][13][14] which is remarkably similar to zizyphusine, and it was also proposed to be one of the potential bioactive components for the treatment of insomnia. [13] In view of this situation, the structure of zizyphusine was reexamined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the pharmacological investigation of ZSS for the treatment of insomnia has mainly focused on rat models. For instance, extensive studies from para-chlorophenylalanine-induced insomnia model rats demonstrated that ZSS aqueous extract (30 g/kg) or ZSS alcohol extract (403.38 mg/kg) signi cantly enhanced the serum concentration of 5-TH and enhanced sleeping behaviors, indicating that the extract was effective in treating insomnia in rats [38,39]. Another main ingredient GABA, one of the major inhibitory neurotransmitters in the nervous system, generates a neuroinhibitory effect by binding with its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep latency was defined as the time between the injection of pentobarbital sodium and the beginning of losing righting reflex loss. Sleep duration was defined as the time from the beginning to the recovery of righting reflex loss (Bian et al, 2021).…”
Section: Pentobarbital Sodium Righting Reflex Testmentioning
confidence: 99%